Agglomeration Economies in the Presence of an Informal Sector The Colombian Case (2018)
This paper analyzes the relationship between agglomeration economies and productivity in the context of a developing country while taking into account the marked presence of an informal sector. Using data from Colombia, we investigate the effect of agglomeration economies on formal and informal productivity. We examine whether the informal sector achieves benefits from agglomeration economies as well as whether there are differences between the formal and informal sectors in terms of agglomeration returns. We find that agglomeration economies, measured by the density of local employment, have a significantly positive effect on productivity in the informal sector, while there is little effect in the formal sector. We estimate an elasticity of wages with respect to employment density of approximately 2% for the informal sector, which implies that informal workers in denser areas will earn approximately 11% more than those in less dense areas.